Genetic diversity of the Central European wild boar (Sus scrofa scrofa) population and domestic pig (Sus scrofa domesticus) breeds based on a microsatellite DNA locus - E. A. Snegin; V. M. Makeeva; A. P. Kaledin; A. M. Ostapchuk; I. D. Alazneli; A. V. Smurov (Вавиловский журнал генетики и селекции, 2022)
The results of studies of the genetic structure of the Central European wild boar (Sus scrofa scrofa) population and four breeds of domestic pigs (Duroc, Yorkshire, Large White and Landrace) bred in the Central Black Earth region of Russia are presented in this work. Based on 12 microsatellite loci, a significant ( p <0.05) decrease in the level of genetic variability in bred breeds was shown. The expected heterozygosity and Shannon index were as follows: in the wild boar, Ho = 0.763 ± 0.026, I = 1.717 ± 0.091; in the Duroc breed, Ho = 0.569 ± 0.068, I = 1.191 ± 0.157; in the Landrace, Ho = 0.618 ± 0.062, I = 1.201 ± 0.147; in the Large White, Ho = 0.680 ± 0.029, I = 1.362 ± 0.074; and in the Yorkshire, Ho = 0.642 ± 0.065, I = 1.287 ± 0.156. The results of checking genotypic Hardy–Weinberg equilibrium based on the G-test of maximum likelihood demonstrated that the overwhelming majority of loci in the wild boar population were in the state of said equilibrium. By contrast, in pig breed populations, some loci demonstrated a significant deviation from the indicated equilibrium. In addition, the Yorkshire, Large White, and Landrace populations had loci, for which the hypothesis of neutrality was reliably rejected based on the results of the Ewens–Watterson test. The revealed private alleles, characteristic of the wild boar and breeds, can later be used to identify them. The ordination of the centroids of different herds in the space of the first two principal coordinates based on the matrix of pairwise estimates of Nei’s genetic distances showed that the most distant populations are the Duroc and Boar breeds, and the most genetically close are the Yorkshire and Landrace breeds. The closest to the wild boar population was the Large White breed. The assessment of the effective size, carried out using the method based on the linkage disequilibrium and the molecular coancestry method, showed that in all studied groups, including the wild boar population, the effective size was less than 100 individuals. The low effective size of the wild boar population (Ne = 21.8, Neb = 4.0) is probably caused by the death and shooting of animals due to Pestis africana suum.